A 10-year trend in income disparity of cardiovascular health among older adults in South Korea. (December 2020) - Lee, Chiyoung; Yang, Qing; Im, Eun-Ok; McConnell, Eleanor Schildwachter; Jung, Sin-Ho; Kim, Hyeoneui
Abstract: Objectives: Although cardiovascular disease (CVD) risk has lessened in Korea, it is unclear whether older adults in all socioeconomic strata have benefited equally. This study explored trends in income disparities in CVD risk among older adults in Korea. Methods: This was a secondary analysis of Korean National Health and Nutrition Examination Survey data (2008–2017), targeting 14, 836 older adults (≥65 years). Socioeconomic position, defined as income and use of welfare benefits, was the primary indicator. The outcome was binary for predicted CVD risk (<90th vs. ≥ 90th). The Slope Index of Inequality (SII) and Relative Index of Inequality (RII) were used to assess trends in disparities. Results: The percentage of older adults with a predicted CVD risk of 90% or more declined over time, but this was due to a decrease among the more affluent. Disparities have persisted since 2012, with a worsening trend seen for Medicaid recipients. We found significant absolute and relative disparities among men over 75 years of age in recent years (SII > 0.19, RII > 7). Conclusions: These results may inform and improve policies regarding income disparity reduction and cardiovascular health. Highlights: Income disparities in CVD risk have persisted since 2012, with a worsening trend seen for Medicaid recipients. Our results highlight the need to improve CVD risk management services offered to the economically disadvantaged. It is important to consider both the absolute and relative terms when examining the disparity trends.